Antidotal Therapeutic Trials of Induced Acute Sulphur Toxicosis in Male Rats - Falah Muosa Kadhim Al-Rekabi (Journal of Global Pharma Technology, 2019)
Objective: The current study is planned for treatment of sulphur acute poisoning as laboratory animals model in male rat. Method: Primarily, oral LD50 estimated by probit method and derived statistically by two different statistic programs, Microsoft excel and Spss version 25, the estimated LD50 was 4102 and 4060 respectively which exhibited no statistical differences. After that the toxic nonfatal dose 3000 mg/Kg.BW was chosen and administered through gastric gavag as a single dose to 18 male rats divided equally and assigned as, G1injected I.P by solution contain (0.6 % sodium nitrate + 6% sodium thiosulfate) plus 0.1 ml B-complex per each 100 gm BW, G2 also injected I.P by barium chloride 160 mg/kg.BW plus 0.1 ml B-complex/100gm .BW, while the third group didn’t receive any anti-dote and considered control group. Results: The result revealed that both anti-dotes have various efficiency to overcome acute sulphur poisoning in rat, but barium chloride plus B-complex was the more efficient one. Conclusion: Barium chloride plus B-Complex I.P antidote is capable to overcome sulphur acute poisoning in rat, but further studies are recommended in ruminantsKeywords: Treatment, Acute, Toxicity, Sulphur, Rat.